ANALYSIS THE EFFECT OF HABIT AND PERCEIVED ENJOYMENT MEDIATED BY BEHAVIOURAL INTENTION TO ADOPTION ON STUDENTS USING MOBILE BANKING BNI - Indah Septiana; Muhartini Salim; Muhammad Yasser Iqbal Daulay (Unib Press Universitas Bengkulu, 2020)
The purpose of this study aims to analyze the effect of habit and perceived enjoyment, mediated by behavioural intention on adoption in students using BNI mobile banking at university of Bengkulu. This research is a casual quantitative study. The total sample of the study is 150 respondents, data were collected using snowball sampling and analyzed using SEM PLS (partial least square). Based on the results of the study explained that habits and perceived enjoyment mediated by behavioural intention support the use of mobile banking at Bengkulu University. This study has several limitations such as, uneven distribution of respondents, and the theoretical scope of research. Subsequent research can determine respondents more evenly, and can expand and modify the research framework to be able to measure or study more deeply about the related variables in this study.Keywords: Habit, Perceived Enjoyment, Behavioural Intention, Adoption.